Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.21608/mjmu.2021.61238.1008
|View full text |Cite
|
Sign up to set email alerts
|

detection of human herpes virus 6&7 in pityriasis rosea and the efficacy of acyclovir

Abstract: Background:The exact aetiology of pityriasis rosea (PR) is still unknown as various researches exist aiming to explain the exact cause. The role of Human Herpes Virus(HHV)-6 & HHV-7 DNA in PR patients has been evaluated in many studies with variable results. The rationale behind the use of antiviral in PR is that the course of the disease follows that of a viral exanthem and also probable involvement of HHV 6 and 7 in its etiopathogenesis. The current case-control study aimed at evaluation of the possible rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…When skin biopsy samples were studied for HHV-6, Watanabe et al [21] detected viral DNA in 12 samples out of 14 cases, similar to the positive study results of Drago et al [24] and Watanabe et al [21] using nested PCR and Broccolo et al [22] using real-time PCR. The studies of Selim et al [14] and Canbolat et al [3] also showed positivity for HHV-7 DNA in tissue samples with significance.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…When skin biopsy samples were studied for HHV-6, Watanabe et al [21] detected viral DNA in 12 samples out of 14 cases, similar to the positive study results of Drago et al [24] and Watanabe et al [21] using nested PCR and Broccolo et al [22] using real-time PCR. The studies of Selim et al [14] and Canbolat et al [3] also showed positivity for HHV-7 DNA in tissue samples with significance.…”
Section: Discussionmentioning
confidence: 88%
“…While seasonal variation, concurrent cases, case clustering, and the observation of virus-like spherical particles on lesional biopsies of the herald patch in electron microscopy studies are the supporting clues, the pathogen has not been identified and real epidemics have not been reported so far. With the present state of knowledge, the benefits of several treatments do not provide strong evidence for or against an infectious etiology [7,14].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation